Relocation of inadequate resection margins in the wound bed during oral cavity oncological surgery: A feasibility study. Issue 7 (1st February 2019) - van Lanschot, Cornelia G.F.; Mast, Hetty; Hardillo, Jose A.; Monserez, Dominiek; ten Hove, Ivo; Barroso, Elisa M.; Cals, Froukje L.J.; Smits, Roeland W.H.; van der Kamp, Martine F.; Meeuwis, Cees A.; Sewnaik, Aniel; Verdijk, Rob; et al.
Abstract : Background: Specimen‐driven intraoperative assessment of the resection margins provides immediate feedback if an additional excision is needed. However, relocation of an inadequate margin in the wound bed has shown to be difficult. The objective of this study is to assess a reliable method for accurate relocation of inadequate tumor resection margins in the wound bed after intraoperative assessment of the specimen. Methods: During oral cavity cancer surgery, the surgeon placed numbered tags on both sides of the resection line in a pair‐wise manner. After resection, one tag of each pair remained on the specimen and the other tag in the wound bed. Upon detection of an inadequate margin in the specimen, the tags were used to relocate this margin in the wound bed. Results: The method was applied during 80 resections for oral cavity cancer. In 31 resections an inadequate margin was detected, and based on the paired tagging an accurate additional resection was achieved. Conclusion: Paired tagging facilitates a reliable relocation of inadequate margins, enabling an accurate additional resection during the initial surgery.